A Systematic Review of Drone Development and Innovation Helps Handling during a Pandemic and Its Challenges for Health Technology - Hapsari, Anindya Ananda; Vresdian, Devan Junesco; Dionova, Brainvendra Widi; Zuhriyah, Halimatuz; Pratama, Legenda Prameswono; Islami, Agnemas Yusoep (Politeknik STMI Jakarta, 2024)
Abstract—These technological advances make researchers around the world develop many new things to support the harmony of life. Humans think a lot, including in terms of technology for the advancement of the times and to maintain life, as well as for handling the unprecedented outbreak of the corona virus that spread in the end of 2019, referred to as COVID-19 by the World Health Organization (WHO), and has put the whole world in a precarious position. The impact of the COVID-19 outbreak, which was witnessed only by Chinese citizens, has become a problem of great concern for almost every country around the world makes the COVID-19 outbreak is spreading tremendous fear, overburdened healthcare system has forced most countries around the world are in a state of partial or complete lockdown. Researchers have begun to develop studies in various fields to help control the virus. Technology is also forced to adapt and develop faster to deal with the existing situation. In response to this action, with this review paper we use trusted sources to present a detailed review of specific aspects related to technological developments during the COVID-19 pandemic, especially UAV or drone technology. In this study we explore the use of technologies such as Unmanned Aerial Vehicles (UAVs) or drones that are modified for handling pandemic situations, and how these technologies are also combined with other trending technologies such as the Internet of Things (IoT), Artificial Intelligence (AI), and 5G, among others, to help reduce their impact from the COVID-19 outbreak and the challenges for the post COVID-19 period. Where UAV technology can be modified and developed according to the needs of the pandemic and development for the post-pandemic and endemic period